National culture and corporate governance: a conceptual review - Ong, Tze San; Adedeji, Babatunji Samuel; Jantan, Amer Hamzah; Rahman, Mohammad Mizanur (Universiti Putra Malaysia Press, 2018)
This book contains thirteen chapters contributed by the authors who specialized in their own areas of business studies. This publication provides a platform for contributors to address the topics of their choices that are generally current in nature. It is also a platform for PhD students to write together with members of their supervisory committees. The readers would find a wide array of findings, conceptual frameworks and suggestions for further research being offered by the respective authors. It is hoped that this book is of great value to the readers for its informative and useful nature. The Chapters in this book contain current challenges and opportunities in the areas of organizational behavior and leadership. The Editor would like to thank all contributors of the chapters for their commitment and dedication; and to the Head of Department of Management and Marketing, Assoc. Prof. Dr. Ho Jo Ann; and the Dean of Faculty of Economics and Management, Professor Dr. Azali Mohamed, for their endless support in making this publication possible